2011
DOI: 10.1016/j.fertnstert.2011.03.084
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-releasing hormone agonist increases expression of osmotic response genes in leiomyoma cells

Abstract: Objective To characterize hyperosmolarity-responsive genes in leiomyoma cells and determine whether gonadotropin-releasing hormone (GnRH) agonist treatment altered their expression. Design Laboratory study. Setting University hospital. Patient(s) None. Intervention(s) Cell culture under hypertonic conditions and with GnRH agonist treatment, RNA isolation, and real-time reverse-transcriptase polymerase chain reaction (RT-PCR). Main Outcome Measure(s) Expression of nuclear factor of activated T cells 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…We have previously demonstrated, in 2D leiomyoma cultures, that GnRH-a have a direct effect on tumor ECM production (19) and osmoregularity (20). The effect on ECM production was not observed until 120 hours of GnRH-a exposure.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We have previously demonstrated, in 2D leiomyoma cultures, that GnRH-a have a direct effect on tumor ECM production (19) and osmoregularity (20). The effect on ECM production was not observed until 120 hours of GnRH-a exposure.…”
Section: Discussionmentioning
confidence: 93%
“…The presence of receptors for GnRH hormones in leiomyomas is further evidenced by the direct regulation of GnRH analogues (GnRH-a) on leiomyoma cell ECM gene expression and protein production in culture (19). The GnRH agonist leuprolide acetate (LA) regulates cellular osmolarity and water transport out of leiomyoma cells grown in culture (20). Clinically, the use of GnRH-a as a part of an adjunct presurgical approach to reduce the size of leiomyomas and increase hematocrit in affected patients has been reported (21).…”
mentioning
confidence: 99%
“…Recent researches showed that NFAT5 is involved in the pathogenesis of multiple cancers including non-small cell lung cancer [24,25], melanoma [26], leiomyoma [27], breast cancer [28e30] and colon carcinoma [31e33]. In non-small cell lung cancer, NFAT5 inhibits cancer cells apoptosis by upregulating HSP-70 [25], but the roles of NFAT5 in proliferation, metastasis and invasion of lung cancer cells have not been stated.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, leiomyomata possess an increased vascularity and fluid content relative to adjacent myometrium (Aleem and Predanic, 1995; Okuda et al, 2008). The increased fluid content is significant because fluid may contribute to the mechanical properties of the tumors and may explain the clinical response of leiomyoma to GnRH agonists and antagonist treatment (Chegini et al, 1996; McCarthy-Keith et al, 2011). Despite the remarkable stiffness of leiomyomata, their altered ECM structure and content, and increased water content, little is known about mechanical signaling in leiomyoma.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found that the Rho-GEF Brx (AKAP13) was not only expressed at high levels in leiomyoma (Rogers et al, 2008), but AKAP13 was also involved in osmotic signaling (Kino et al, 2009) and osmotic signaling was altered in leiomyoma cells (McCarthy-Keith et al, 2011). Taken together, these observations suggest that altered mechanical signaling in leiomyoma involves RhoA and that altered viscoelastic properties contribute significantly to the increased stiffness characteristic of the tumors.…”
Section: Introductionmentioning
confidence: 99%